Feeling/hearing, thinking/expressing, making geo-graphies: Multiple geographies of affect in dialogue with a great geographer of action - HAESBAERT, Rogério (Utopía y Praxis Latinoamericana, 2024)
This article integrates the affective and intellectual dimensions of our relationship with Carlos Walter Porto-Gonçalves, regarded here as a great geographer of action, both in terms of the concrete actions of social groups and movements and the transformative action of emotions. In this way, multiple territorialities (or multiterritorialities) are constructed between feeling/listening, thinking/expressing, and geographical actions, in the dialogue between Carlos Walter’s rich contributions and our own work, particularly concerning territory as a process in the "conduct of conduct" that encompasses not only traditional politics but also its expansion into the realm of the "more-than-human," which increasingly impacts and (de)territorializes us.